Impact of compact fluorescent lamp in term of total harmonic [electronic resource] distortion - Mohd. Hafifi Rahmat, 1988-; Mohd Fadli Rahmat (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011